Facies associations, detrital clay grain coats and mineralogical characterization of the Gironde estuary tidal bars: A modern analogue for deeply buried estuarine sandstone reservoirs. (April 2020) - Virolle, Maxime; Féniès, Hugues; Brigaud, Benjamin; Bourillot, Raphaël; Portier, Eric; Patrier, Patricia; Beaufort, Daniel; Jalon-Rojas, Isabel; Derriennic, Hervé; Miska, Serge
Abstract: Estuarine tidal bar sandstones are complex reservoir geobodies commonly exploited by the oil and gas industry. In order to better predict the reservoir potential of these geobodies, this study provides a modern-day reservoir analogue, describing tidal bars in the inner and outer Gironde estuary from the microscopic to the macroscopic scale. The originality of this work lies in the multi-scale study of modern estuarine tidal bars based on numerous piston cores extracted in a high-energy environment. This work demonstrates that these tidal bars are composite sedimentary bodies made up of individual reservoir sand units separated by thick muddy layers. Their vertical facies associations and internal architectures are controlled by local hydrodynamic variations and seasonal river influxes. Detrital clay grain coats are notably characterized using a portable and handheld mineral spectrometer from the base to the top of the tidal bars. X-ray diffraction and electron microscopes reveal that these coats are mainly composed of di-octahedral smectite, illite, chlorite and kaolinite associated with other components such as diatoms or pyrite. The best reservoir geobodies are those with the minimum clay permeability barriers at the macro and mesoscale. An optimum coated grain content and clay fraction volume is also needed for generating authigenic clay coatings and inhibiting quartz overgrowth. These conditions are met within the tidal sand bars of the outer estuary funnel that are expected to be the best reservoir geobodies in deeply buried sandstones. Highlights: Within estuarine sandstones reservoirs, best reservoirs properties are found downstream of the TMZ. Hydrodynamic processes in very turbid estuaries influence tidal bars vertical facies associations. Coats can be found down to a depth of 7 m within modern estuarine tidal bars. We tested the use of a portable and handheld spectrometer to detect clays in sands. Ideal initial conditions: A clay content of 25 wt% at most, a coated grain content of 15%, a coat coverage of 10%.